1995
DOI: 10.1111/j.1469-8137.1995.tb03032.x
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of arbuscular mycorrhizas and short‐term cold exposure on wheat

Abstract: SUMMARYIn order to investigate the eflect of arbuscular mycorrliizal colonization and short-tenn cold exposure on Triticum aestivum L., 7-vvk-old seedlings of spring and winter cultivars (Glenlea and AC Ron) were submitted to a 1-wk cold treatment when inoculated with Glomus mosseae (Nicol. & Gerd.) Gerd. & Trappe. The combined effect of arbuscular mycorrhizas and low temperature on the two cultivars was determined for several physiological parameters including biomass and chlorophyll, protein, and sugar conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 39 publications
4
15
0
1
Order By: Relevance
“…Our study found that AM colonization could enhance chlorophyll concentration of maize leaves at both optimal and suboptimal temperatures, which was in agreement with the results of wheat under cold stress by Paradis et al (1995). However, Charest et al (1993) found that mycorrhizal maize had lower chlorophyll concentration than non-mycorrhizal plants.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our study found that AM colonization could enhance chlorophyll concentration of maize leaves at both optimal and suboptimal temperatures, which was in agreement with the results of wheat under cold stress by Paradis et al (1995). However, Charest et al (1993) found that mycorrhizal maize had lower chlorophyll concentration than non-mycorrhizal plants.…”
Section: Discussionsupporting
confidence: 94%
“…Also, mycorrhizal root colonization changes under low temperature (Hayman 1974;Hetrick and Bloom 1984;Liu et al 2004). AM colonization could affect leaf water potential of bean plants (EI-Tohamy et al 1999), chlorophyll concentration in the leaves of maize (Charest et al 1993) and wheat plants (Paradis et al 1995). It's well known that temperature, water and photosynthesis are extremely important to plants growth and productivity.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…), Andersen et al (1987) found greater relative leaf area and growth rates of arbuscular mycorrhizal seedlings compared with rates for non-mycorrhizal seedlings at 7.5 and 11.5°C, similar rates at 15.5°C, and greater rates in non-mycorrhizal seedlings at 20°C. Paradis et al (1995)• found that mycorrhizal wheat plants had higher concentrations of chlorophyll and non-reducing sugars than non-mycorrhizal at 5 but not at 25°C. Zhang et al (1995) examined sub-optimal root zone temperatures and the development of the soybean-AM…”
Section: Temperaturementioning
confidence: 99%
“…Arbuscular mycorrhizal (AM) symbiosis is a very ancient interaction between plant roots and zygomycetes fungi (Morton & Benny 1990). It is believed that AM symbiosis occurs in over 90% of terrestrial plants; it significantly increases tolerance to drought, nutrient deficiency, cold or warm temperature, and, in some cases, heavy metal contamination , Davies et al 2001, Paradis et al 1995, Subramanian et al 1997, Subramanian & Charest, 1998. Recent phytoremediation studies that incorporated the AM-variable have had mixed findings.…”
Section: Introductionmentioning
confidence: 99%